ANALISA POSTUR KERJA UNTUK MENGURANGI KELUHAN MUSCULOSKELETAL DISORDERS PADA PEKERJA CV. BALIKPAPAN DIESEL - Nisrina, Fardela Najla; Zulfikar, Iwan (IDENTIFIKASI, 2018)
Complaint of musculoskeletal was being trend of disease which connected with occupation around the world in developing countries and industrial countries. One of occupation who has activities MSDs complaint is CV. Balikpapan Diesel with cleaning up fuel injection pump with bond of facilities and duration of cleaning up is more than 2 hours each days. Based on calculation work posture risk level respondens with REBA (Rapid Entire Body Assessment) method, major responden on middle level as much as 70% who need check up and dangerous position change. And complaint level Musculoskeletal Disorders (MSDs) with Nordic Body Map, dominant respondence on middle level as much as 70% which mean still need repair action at the other day, with result all respondence (100%)had complaint at upper neck, backbone, waist, hip and butt.